2016
DOI: 10.1038/mtna.2016.98
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Ureagenesis in Hepatocytes by CRISPR/Cas9-mediated Genomic Addition to Arginase-deficient Induced Pluripotent Stem Cells

Abstract: Urea cycle disorders are incurable enzymopathies that affect nitrogen metabolism and typically lead to hyperammonemia. Arginase deficiency results from a mutation in Arg1, the enzyme regulating the final step of ureagenesis and typically results in developmental disabilities, seizures, spastic diplegia, and sometimes death. Current medical treatments for urea cycle disorders are only marginally effective, and for proximal disorders, liver transplantation is effective but limited by graft availability. Advances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…The majority show excellent molecular correction, but fail to prove fully functional phenotypic correction resembling mature primary hepatocytes. Specifically, some researchers have used fetal, instead of adult, hepatocytes for comparison, while others fail to show the rescue of phenotype [ 40 , 41 ]. In this study, the ratio of labelled to total urea produced by unedited and edited iPSC-HLC was quantified by mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…The majority show excellent molecular correction, but fail to prove fully functional phenotypic correction resembling mature primary hepatocytes. Specifically, some researchers have used fetal, instead of adult, hepatocytes for comparison, while others fail to show the rescue of phenotype [ 40 , 41 ]. In this study, the ratio of labelled to total urea produced by unedited and edited iPSC-HLC was quantified by mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…After we submitted this manuscript, Lee et al . 41 reported a CRISPR/Cas9-based strategy utilizing exon 1 of the hypoxanthine-guanine phosphoribosyltransferase (HPRT) locus to genetically modify and restore arginase activity using hyperargininemic patient-derived cells. In line with our current study, their differentiated hepatocyte-like cells co-express Afp and Alb, indicating an immature phenotype as opposed to adult hepatocytes, which is also typically found in many differentiation cultures of mouse and human cells to date.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, conditions were refined for RGN-mediated AAVS1 -TI, and it was found that excluding Cas9 expression from G1 phase of the cell cycle significantly enhanced HDR-mediated integration at the locus [ 69 ]. The HPRT locus served as safe harbor for therapy in iPSCs of a patient with ARG1 -linked urea cycle disorder [ 70 ]. The strategy targeted exon 1 of HPRT for integration of a construct holding both a puromycin resistance expression cassette and an ARG1 cDNA driven by the EF1α promoter.…”
Section: Rare Repair: Employing the Molecular Toolkitmentioning
confidence: 99%